Monday

March 2, 2015

March 2, 2015

Posted by **eddie** on Tuesday, May 8, 2012 at 11:42am.

- Calculus -
**MathMate**, Tuesday, May 8, 2012 at 1:30pmFrom

4x + 5y – 3 = 0

Divide all coefficients by sqrt(4^2+5^2) to get

4x/sqrt(41) +5y/sqrt(41) - 3/sqrt(41) = 0

where

3/sqrt(41) = length of normal

cos(θ)=4/sqrt(41), and

sin(θ)=5/sqrt(41)

Note: the normal form is given by:

x cos(θ) + y sin(θ) - p =0

where |p|=length of normal.

**Answer this Question**

**Related Questions**

Precalculus check answers help! - 7.) Write the equation 3x + 4y – 7 = 0 in ...

Precalculus check answers help! - 1. Which expression is equivalent to cos ...

Math - Find the angle the normal makes with the positive x–axis. 1. 3x – 2y – 1...

calculus - Find the points of the paraboloid z=x^{2}+y^{2}-1 at which the normal...

calculus - Find the points of the paraboloid z=x^{2}+y^{2}-1 at which the normal...

Calculus - Can anybody help me with this? Consider the surface xyz = 20. A. Find...

physics - A particle undergoes two displaments , measured from the positive x-...

equation of the normal - An equation of the normal to the graph of f(x) = x / (...

Physics - A 5.5-kg box is under an upward force of 45 N which makes a 60o angle...

Physics - I'm tyring to undersatnd uh motion of a particle at an incline on a ...